The effects of trade liberalisation on imports in selected developing countries - Amelia U. Santos-Paulino (University of Kent, Department of Economics, 2001)
This paper analyses the impact of the reduction of tariff and non-tariff barriers on the imports of selected developing countries, utilising dynamic panel data techniques. Domestic income and relative prices are found to be significant determinants of import growth. Additionally, the results indicate that import duties reduce import growth, but the effect varies according to the region and the type of trade policy regime existing in the country. The results also show that the elimination of trade policy distortions has a strong, positive impact on import growth. Lastly, it is found that income and price elasticities are higher as a result of trade policy reform.
Keywords: C21; C22; C23; F13; F14; 330; trade liberalisation; import growth; dynamic panel data; time series/cross section; developing countries; Außenhandelsliberalisierung; Import; Entwicklungsländer